Pengungkapan emisi karbon dan kinerja perusahaan: Apakah ukuran perusahaan penting? - Krisyadi, Robby; Volensya, Joslyn; Ramadana, Mariska (Jurnal Akuntansi dan Manajemen, 2026)
Firm performance reflects a company’s effectiveness in managing resources to achieve economic objectives and create value for stakeholders. In modern business practices, carbon emission disclosure has become increasingly important as a form of environmental transparency that can influence investor perception and trust. This study examines the effect of carbon emission disclosure on firm performance, with firm size as a moderating variable. The analysis uses annual reports and financial statements of companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period, processed using Stata software. The findings show that carbon emission disclosure has a positive and significant effect on firm performance, indicating that greater disclosure is associated with improved financial outcomes. However, firm size significantly moderates this relationship in a negative direction, meaning that the positive influence of carbon emission disclosure on firm performance tends to weaken in larger firms. These findings contribute to the literature on financial performance and sustainability by highlighting the importance of environmental transparency in enhancing firm value. Practically, the results encourage firms to disclose environmental information more extensively and support policymakers in strengthening regulatory frameworks to promote sustainable business practices.